Percepção ambiental dos estudantes da Escola Família Agrícola no município de Seabra-BA - Veimrober Junior, Lucio Aderito dos Anjos (2014)
Environmental education should aim social transformation of character that seeks urgent as Sorrentino (2005), overcoming the environmental and social injustices in humanity. The need for environmental awareness in people requires an awareness regarding the care of neighbor and the environment, thus balancing thus the attitudes of the individual in the community operates. Within the Agricultural Family Schools, Environmental Education (EE) provides students with critical knowledge on a more sustainable type of agriculture, the dangers of using pesticides and that these substances cause harm to human health, animals and ecosystems. Additionally, draws attention to the inclusion of a more just economy, solidarity economy related to agroecology. The Agricultural Family Schools have principles as the four elements: the development of the medium; comprehensive education; pedagogy of alternation; and local associations, and these are divided into ends and means, and are used to achieve the objectives, which are local associations and the pedagogy of alternation. The current model of agricultural production have brought several actions degrading the environment and man's field. As a research methodology field research was conducted with questionnaires regarding the theme of environmental awareness in rural areas. This monograph got a diagnosis of environmental perception of the students of the Agricultural Family School in the municipality of Seabra, Bahia state as a means of social transformation in the middle peasant.. The research concluded that there is a need for further exploration on the theme of environmental education in rural areas with students, especially when dealing with the transition from conventional agriculture to more sustainable agriculture, the need to better understand the importance of the environment.